2018
DOI: 10.7717/peerj.5409
|View full text |Cite
|
Sign up to set email alerts
|

A buoyancy, balance and stability challenge to the hypothesis of a semi-aquaticSpinosaurusStromer, 1915 (Dinosauria: Theropoda)

Abstract: A recent interpretation of the fossil remains of the enigmatic, large predatory dinosaur Spinosaurus aegyptiacus Stromer 1915 proposed that it was specially adapted for a semi-aquatic mode of life—a first for any predatory dinosaur. To test some aspects of this suggestion, a three-dimensional, digital model of the animal that incorporates regional density variations, lungs and air sacs was generated, and the flotation potential of the model was investigated using specially written software. It was found that S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 41 publications
1
41
4
2
Order By: Relevance
“…Recently, potential semi-aquatic lifestyles have been hypothesised for a small number of dinosaurs 18,19 . However, the only group of dinosaurs for which multiple plausible lines of evidence indicate aquatic adaptations are the spinosaurids, large-bodied theropods interpreted as near shore waders that fed on fish along the margins of, rather than within, water bodies 10,15,20 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, potential semi-aquatic lifestyles have been hypothesised for a small number of dinosaurs 18,19 . However, the only group of dinosaurs for which multiple plausible lines of evidence indicate aquatic adaptations are the spinosaurids, large-bodied theropods interpreted as near shore waders that fed on fish along the margins of, rather than within, water bodies 10,15,20 .…”
mentioning
confidence: 99%
“…A recent reappraisal of the largest known spinosaurid, Spinosaurus aegyptiacus, identified a series of adaptations consistent with a semi-aquatic lifestyle, including reduced hindlimbs, wide feet with large, flat unguals, long bones with a highly reduced medullary cavity, and a suite of cranial features such as retracted nares, interlocking conical teeth, and a rostromandibular integumentary sensory system 7 . This interpretation has been challenged on the basis of taphonomy 8 , biomechanical modeling 10 , and anatomical concerns 8 . Locomotion in water is a major point of contention 10,11 , because no unambiguous evidence for a plausible mode of propulsion has been presented.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we performed a linear regression on the replacement vs. formation rate plots in order to predict the tooth replacement rate of the spinosaurine based on the maximum tooth formation rate. The body mass for the spino-saurid was taken from Henderson (2018), all other data were taken from Erickson (1996a) Table 2). The regression was done on the total data set and on a data set including only theropods (Table 2, Appendix 1).…”
Section: Methodsmentioning
confidence: 99%
“…Isotopic data suggested a semi-aquatic lifestyle for spinosaurs (Amiot et al, 2010), although some spinosaur teeth were found with a similar isotopic signal as other terrestrial theropods. Ibrahim et al (2014;2020) suggested anatomical features, such as the retraction of the fleshy nostrils, modifications in the pelvic girdle and hind limbs, and a propulsive tail to also support a semi-aquatic life style and associated piscivory, although their reconstruction of Spinosaurus as a semi-aquatic animal has been criticized on anatomical (Evers et al, 2015) and biomechanical reasons (Henderson, 2018). Similarly, Gimsa et al (2016) put forward a new hydrodynamic hypothesis concerning the function of the back sail of Spinosaurus, but this hypothesis was also made rather unlikely by the biomechanical considerations of Henderson (2018).…”
Section: Predatory Adaptationsmentioning
confidence: 99%